The comparative influence of climate change and demography in spatially distributed degree-day projections for France in the 21st century - Sylvain Cros; Philippe Drobinski; Louis-Gaëtan Giraudet; Johann Meulemans (Climate Services)
Heating and cooling in households account for half of global energy use and a significant part of global greenhouse gas (GHG) emissions. These figures are expected to change significantly under the joint influence of climate change and demography. We assessed the respective contribution of each of these processes in mainland France, a country presenting heterogeneous climate and currently low ownership of air conditioners. We projected heating degree days (HDD) and cooling degree days (CDD) up to 2100 using EURO-CORDEX simulations and considering three sources of uncertainty: three different methods for computing HDD and CDD; two emission scenarios (RCP4.5 and RCP8.5); and two population projections. We found a net increase in energy demand by 2100, driven by a slight decrease in HDDs and a strong increase in CDDs. Climate and population have a similar influence on net aggregate energy demand, however with statistically significant differences from a French department to an other. In particular, climate change has a particularly strong influence on HDDs in Atlantic and Mediterranean coastal regions after 2070. In turn, CDDs appear more evenly impacted by climate change and population increase, except in Southern cities where population is growing fast. In any case, the ranking between the two influences is strongly sensitive to population projections scenarios. This influence distinction is useful to apply a differentiated energy policy: energy efficiency measures are more effective for climate-driven demand increases, while behavioural policies are better suited for population-driven ones.